Comparing the CT and MRI findings for canine primary hepatocellular lesions. (8th November 2021) - Kurokawa, Shohei; Tanaka, Toshiyuki; Yamazaki, Hiroki; Noguchi, Shunsuke; Wada, Yusuke; Nishida, Hidetaka; Akiyoshi, Hideo
Abstract: Background: Triple‐phase CT and gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid (Gd‐EOB‐DTPA) MRI have been used to differentiate hepatocellular carcinomas (HCCs) in dogs. Methods: This retrospective case series aimed to compare the CT findings with MRI findings of 20 canine hepatocellular lesions, including eight poorly/moderately‐differentiated HCCs, eight well‐differentiated HCCs and four hyperplasias. CT data were analysed, and the following parameters were noted: vessel enhancement, enhancement pattern in the equilibrium phase, maximal transverse diameter, the lowest enhancement, and the attenuation values of each hepatocellular lesion in the precontrast and triple‐phase series, including the arterial phase, portal phase and equilibrium phase. MRI data were analysed, and the following parameters were noted: signal intensities of each hepatocellular lesion on T2‐weighted images and T1‐weighted images, and signal intensity ratio of the hepatocellular lesions in the hepatobiliary phase. Results: In 62.5% of poorly/moderately‐differentiated HCC and 75% of well‐differentiated HCC, presumptive necrosis was detected on CT and MRI. In the hepatobiliary phase on MRI, the median signal intensity ratio of poorly/moderately‐differentiated HCC (0.54 [range: 0.3–0.71]) was significantly lower than that of well‐differentiated HCC (0.75 [range: 0.6–0.96]) and hyperplasia (0.79 [range: 071–0.98]; p  = 0.02 and p  = 0.02, respectively). Conclusion: Gd‐EOB‐DTPA‐enhanced MRI may be a superior modality for differentiating hepatocellular origin lesions.